PENGARUH MODEL PEMBELAJARAN INKUIRI TERBIMBING TERHADAP KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK PADA PEMBELAJARAN BIOLOGI - Tita Sonia; Heffi Alberida; Fitri Arsih; Ganda Hijrah Selaras (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2023)
The guided inquiry learning model is a learning model that can increase student activity. Activeness in the learning process can be seen from the critical thinking skills possessed by students. Measurement of critical thinking skills is needed so that teachers can develop learning steps to improve students' critical thinking skills. This research is an experimental research. The purpose of this study was to determine the effect of the guided inquiry learning model on students' critical thinking skills. The population in this study were all students in class XI MIPA at SMA Negeri 2 Payakumbuh for the 2021/2022 academic year. The research samples were students of class XI MIPA 7 and class XI MIPA 8 which were determined by lottery technique. Data analysis used paired sample t-test analysis with the help of the SPSS 26 for windows program. The results of data analysis showed that the average gain score in the experimental group was 37.83 while that of the control class was 22.23. The application of the guided inquiry learning model has a positive effect on students' critical thinking skills. The results of the study show that the guided inquiry learning model can improve students' critical thinking skills.